The illusion of history : time and the radical political imagination - Russ, Andrew R., 1979- (Catholic University of America Press, 2013)
In this book, the author argues that a closer look at their philosophical underpinnings finds that Rousseau, Marx, and Foucault are much less "historical" in their methodology than is widely believed. Instead, they share a more "timeless" view, one indebted to principles ordinarily seen as timeless or transcendent.